2002
DOI: 10.1111/j.1523-1755.2002.kid590.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in renal ischemia-reperfusion injury in rats: Possible role of endothelin

Abstract: Female rats enjoy relative protection against postischemic renal failure. Furthermore, in intact males the effects of androgens upon ischemic kidney damage seem to be mediated by endothelin-induced vascular changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
65
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(76 citation statements)
references
References 33 publications
9
65
1
1
Order By: Relevance
“…1b). These results, consistent with previous observations [5, 6], demonstrate the resistance of female animals to ischemic ARF.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…1b). These results, consistent with previous observations [5, 6], demonstrate the resistance of female animals to ischemic ARF.…”
Section: Resultssupporting
confidence: 83%
“…Recent studies by Szabo and colleagues have suggested that female rats are more refractory to ischemic ARF than male rats [5, 6]. Importantly, this experimental observation seems to be consistent with some of previous clinical analyses [7, 8].…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…The gender differences had been documented in the studies of other ARF models. For instance, female rats were more refractory to ischemic ARF than male rats [19], whereas female rats appeared more sensitive to cisplatin-induced ARF [20]. According to these studies, the sex hormone was considered an important reason for this difference.…”
Section: Discussionmentioning
confidence: 99%